Autologous stem cell transplantation for relapsed/refractory diffuse large B-cell lymphoma: efficacy in the rituximab era and comparison to first allogeneic transplants. A report from the EBMT Lymphoma Working Party - Robinson, Stephen; Boumendil, A.; Finel, H.; Blaise, D.; Poiré, X.; Nicolas-Virelizier, E.; Or, R.; Malladi, R.; Corby, A.; Fornecker, L.; Caballero, D.; Pohlreich, D.; et al. (Bone marrow transplantation, 2016)
In the era of chemoimmunotherapy, the optimal treatment paradigm for relapsed and refractory diffuse large B-cell lymphoma has been challenged. We reviewed the outcome of standard salvage therapy with an autologous stem cell transplant (autoSCT) over the last two decades and the outcome of allogeneic SCT (alloSCT) in the most recent decade. AutoSCT recipients diagnosed between 1992 and 2002 (n=2737) were compared with those diagnosed between 2002 and 2010 (n=3980). Patients diagnosed after 2002 had a significantly lower non-relapse mortality (NRM) and relapse incidence (RI) and a superior PFS and overall survival (OS). A total of 4210 patients diagnosed between 2002 and 2010 underwent either an autoSCT or an alloSCT as their first transplant procedure. Two-hundred and thirty patients received an alloSCT (myeloablative (MACalloSCT) n=132, reduced intensity (RICalloSCT) n=98). The 4-year NRM rates were 7%, 20% and 27% for autoSCT, RICalloSCT and MACalloSCT, respectively. The 4-year RI was 45%, 40% and 38% for autoSCT, RICalloSCT and MACalloSCT, respectively (NS). The 4-year PFS were 48%, 52% and 35% for autoSCT, RICalloSCT and MACalloSCT, respectively. The 4-year OS was 60%, 52% and 38% for autoSCT, RIC alloSCT and MACalloSCT, respectively. After adjustment for confounding factors NRM was significantly worse for patients undergoing alloSCT whilst there was no difference in the RI.
Published online 30 November 2015
Gesehen am 30.04.2020